Onto/Epistemic Violence and Dialogicality in Translanguaging Practices Across Multilingual Mathematics Classrooms - Chronaki, Anna; Planas, Núria; Svensson Källberg, Petra (Teachers College record (1970), 2022)
Background: The focus on translanguaging practices in multilingual classrooms can be seen, by and large, as responding to risks of violence entailed in diverse contexts of language use, including the teaching and learning of mathematics. However, the practice of translanguaging alone cannot counteract the hegemonic authority of our relation to language curricula being present through interactions among teachers, students, and researchers, as well as material resources. Purpose: Drawing on Bakhtin’s philosophy of language, we discuss dialogicality as a critical and democratic organizing principle for the pervasive polyphony that characterizes every utterance constituting heteroglossia. Dialogicality reconstitutes our relation to language through the “other” and the need to see any utterance as a nonteleological process among subjects and objects. As such, the aim is to explore how acts of dialogicality may address the potential risks of onto/epistemic violence in translanguaging practices. Focusing on either emergent or orchestrated translanguaging in three European states: Greece, Catalonia and Sweden, we discuss how dialogicality allows for alternative accounts of language use in complex classroom events. Method: Methodologically, we start by encountering the sociopolitical context of monolingual and monologic curricula in Europe, where the three cases we theorize take place, along with our considerations for dialogicality in the realm of translanguaging. Our theorizing-in-practice unfolds a double effort in reading. First, what can we read today as risks of onto/epistemic violence in each of these cases? And second, what is the potential of dialogic translanguaging across the cases and within the boundaries of state monolingual policy and monologic discursive culture of school mathematics? Findings: The present article contributes by discussing dialogicality as a relational onto/epistemology toward addressing translanguaging practices. Concerning the first question, our theorizing-in-practice shares evidence of the inevitable presence of onto/epistemic violence in every utterance. The limited scope of a crude mathematisation process through language appears continuously in mathematics classrooms, serving to place either the object or the subject into fixed narratives. Regarding the second question, our dialogical reading of translanguaging denotes the importance of the importance of minor responding(s) to such moments of violent risk. We understand them as “cracks” in the authoritative status of monolingual and monologic mathematics curricula; we argue that such minor, yet crucial, cracks are of great significance for creating acts of dialogicality from “below,” disrupting the hegemonic authority of an assumed neutral mathematical language. Conclusions/Recommendations: The risk of onto/epistemic violence is inevitable in any discursive and embodied encounter in multilingual mathematics classrooms, including the translanguaging practices. The study suggests that acts of dialogicality become minor responses to violence in ways that both counteract oppressive monologic discourse and open toward a relational onto/epistemology with mathematics, children, teachers, material resources, and researchers. Remembering how Bakhtin insisted that “language is never unitary” and “dialogue” is not a panacea, we emphasize the need for a continuous focus on creating acts of dialogicality with language and discourse.